2021
DOI: 10.1016/j.sjbs.2020.11.068
|View full text |Cite
|
Sign up to set email alerts
|

Induction of liver fibrosis by CCl4 mediates pathological alterations in the spleen and lymph nodes: The potential therapeutic role of propolis

Abstract: In an animal models, carbon tetrachloride (CCl 4 ) is a carcinogenic agent that causes liver fibrosis. The current study aims to investigate whether induction in liver-fibrosis by CCl 4 in the mouse model could promote the initiation of fibrosis in lymph node and spleen due to sustained increase of inflammatory signals and also aimed to clarify the protective therapeutic effects of propolis. The male mice (BALB/c) were categorized into three experimental sets and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…In this study, the toxicity of CCl4 in rats was manifested by an increase in the level of liver enzymes, serum lipids, TNF-α, CRP, WBC, ACE, urea and creatinine with decreased serum proteins, hemoglobin and FBW constituent with histopathological changes in the liver, kidney and spleen tissues. These results have been supported previously [6]. The detection of elevated level of serum aminotransferases is mostly indicated as abnormal liver function existing in the hepatic cells which indicates structural changes in the hepatic tissues and biliary system [27].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this study, the toxicity of CCl4 in rats was manifested by an increase in the level of liver enzymes, serum lipids, TNF-α, CRP, WBC, ACE, urea and creatinine with decreased serum proteins, hemoglobin and FBW constituent with histopathological changes in the liver, kidney and spleen tissues. These results have been supported previously [6]. The detection of elevated level of serum aminotransferases is mostly indicated as abnormal liver function existing in the hepatic cells which indicates structural changes in the hepatic tissues and biliary system [27].…”
Section: Discussionsupporting
confidence: 80%
“…Chemicals that cause liver injuries are called hepatotoxins [3] such as CCl 4 that has been frequently used in experimental rodent animals for inducing liver damage [4]. It has been recently reported, that in addition to the liver, CCL 4 can induce damages in other organs such as the kidney and spleen [5][6]. However, this deterioration can be avoided naturally by some essential oils obtained from different plants [7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, secondary lymphoid organs showed a significant increase in the circulation of T and B cells as well as intracellular levels of TGF-β, Nrf2, COX-2, eNOS, ROS, NO, and proinflammatory cytokines. Propolis treatment caused substantial suppression of liver collagen deposition, inflammatory signaling cascades suggesting its benefits against fibrotic complications and cancer [ 46 ]. Cancer chemotherapy has been shown to induce cognitive dysfunction by induction of oxidative stress and neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, melatonin treatment protects lymphoid organs from diabetic effects (Ozkanlar et al 2016 ). Similarly, Sayed et al ( 2021 ) observed that propolis supplementation decreased collagenous fibers in the lymphoid organs of CCl4-treated animals.…”
Section: Discussionmentioning
confidence: 78%